«Подольские епархиальные ведомости» як джерело з церковної історії Поділля - Григорук, О. (Інститут історії України НАН України, 2009)
У статті міститься джерелознавча характеристика «Подольських епархиальных відомостей» - офіційного друкованого органу Подільської єпископської кафедри 1862-1905 рр.: проаналізовано суспільно-політичні та цензурні умови функціонування видання, розкрито його структуру, ідеологічні засади, жанрове та тематичне розмаїття публікацій часопису. In this article we give the general description of the resources of «Eparchy notions of Podillya» – the official printed document of the Bishop Faculty of Podillya: social-political and censorial conditions of this document’s functioning were characterized; its structure, ideological ambushes and genre picularities were analyzed; the variety of topics and the problems of the church and national-spiritual life of Podillya were represented.